How many manufacturing firms are there in Mozambique? - Søren Schou; José Cardoso (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper addresses the issue of poor data on Mozambican manufacturing firms. A new dataset (the merged manufacturing database) is merged from provincial industrial databases from each of Mozambique's 11 provinces. The new dataset is assessed by comparing it to the latest manufacturing enterprise survey as well as the latest firm census. The merged manufacturing database is found to provide a somewhat accurate picture of small, medium, and large firms, but many micro enterprises are not found on the list. Realizing this, the population of manufacturing firms in Mozambique by size and province is estimated using imputation methods. Finally, the degree of representativeness of the two latest enterprise surveys (IIM2012 and the survey used for the latest investment climate assessment) is revisited using the new population estimate.
Keywords: C81; O14; O17; 330; census; industry; Mozambique